From Strategy to Success: Competitive Strategy Canvas of Serena Skin and Wellness in the Cosmetic Clinic Industry - Rosali, Alexandrina Everdine; Malinda , Maya (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the strategic approach used by Serena Skin and Wellness, a cosmetic clinic operating in the highly competitive Indonesian aesthetic healthcare market. Using a qualitative methodology, the study applied the Competitive Strategy Canvas (CSC); the FORMAT-BIDES framework to analyze how clinics leverage technological innovation, cultural integration, and sustainability to achieve competitive advantage. Data was collected through interviews, observations, social media analytics, and document analysis. These findings reveal that Serena Skin has managed to differentiate itself through the integration of AI-powered dermatological diagnostics and traditional Balinese health rituals, supported by eco-friendly operations and strategic partnerships. The clinic's focus on specific demographics of urban millennials and Gen Z, combined with personalized membership programs and digital branding initiatives, has significantly increased customer loyalty and brand visibility. This study contributes to a broader discourse on the competitiveness of MSMEs by showing that holistic and contextual innovation strategies can drive long-term value creation in service-based industries. Future research may explore scalability and financial performance metrics to validate these findings in various market contexts